(untitled) (Research, Society and Development, 2023)
Introduction: The maintenance of quality of life for the elderly presents several challenges, especially frailty. This process resulting from metabolic and physiological changes is currently evaluated by different parameters, from sarcopenia to functional disability. Objective: We sought to evaluate the studies in the literature about the impact of frailty, as well as to understand the instruments for its definition and the impact on the lives of individuals, analyzing means of prevention of these implications and preservation of health. Methodology: A review of narrative literature with descriptive analysis was carried out, using the descriptors quality of life; elderly; sarcopenia; daily activities; geriatric evaluation. Results: 60 articles were analyzed, separated and tabulated according to the study design. It was observed that through the various existing criteria for defining frailty, there is a positive correlation between this syndrome and quality of life in the elderly. Conclusion: It was demonstrated that through health protocols assists in the direction and proper conduct of people with frailty, enabling more well-being to aging.